What's in the middle? Two voices or three in Anicent Greek? - Horrocks, Geoffrey C. (Keria (Ljubljana), 2020)
It has long been taken for granted in reference works, grammars and elementary introductions that Ancient Greek had three grammatical voices, active, passive and middle. Yet scholars have always had great difficulty in characterising the middle voice in a straightforward and convincing way, and language learners are often perplexed to find that most of the middles they find in texts fail to exemplify the function, usually involving some notion of self interest, that is typically ascribed to this voice. This article therefore re-examines the Ancient Greek middle, both through the lens of a general survey of "middle voice" functions across languages, and through the analysis of all the medio-passive verb forms attested in Book 1 of Plato's Republic. The principal observations are that Ancient Greek middles do not represent a regular pattern of usage either from a typological point of view or as employed specifically in Republic 1 (the database is in fact partly extended to other works). Accordingly, the main conclusion is that the Ancient Greek middle is not a grammatical voice sensu stricto, i.e. a regular syntactic alternation applying to all verbs with a given set of properties and expressed by a regular morphological form with a predictable semantic function. Rather, it appears to be a convenient collective name for a large set of "autonomous" verb forms that are either clearly deponent (i.e., have no active counterparts) or that have been lexicalised in a specialised meaning vis-a-vis their supposed active counterparts (i.e., are also deponents in practice, despite appearances). In all probability, therefore, medio-passive morphology, whatever it once represented in terms of function, was recharacterised prehistorically as "passive" morphology, leaving a residue of verbs exhibiting forms with non-passive functions. Presumably, these survived as "middles" only because they had no active counterparts or had been assigned innovative meanings that distinguished them from any formally related actives.
Keywords: active voice; aktiv; Ancient Greek; deponent verb; deponentniki; medij; middle voice; pasiv; passive voice; pomenska specializacija; semantic specialisation; stara grščina